ANALYSIS OF L-THEANINE ON GENE EXPRESSION ON UNPREDICTABLE CHRONIC MILD STRESS INDUCED NEURONAL DAMAGE IN WISTAR RATS - RITHANYA M; UMAR DAWOOD J; KARTHIK GANESH MOHANRAJ (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The modulatory role of L-theanine on the regulation of gene expression in unpredictable chronic mild stress (UCMS) induced neuronal impairment in rats is the primary objective of this study. Methods: Adult male Wistar rats were distributed into 6 groups: control, fluoxetine alone, L-theanine alone, UCMS, UCMS+fluoxetine, and UCMS+L-theanine. UCMS was induced for 40 days using a variety of mild stressors. From the 41st day, the respective drug treatment was given for 30 days as per the groupings. Fluoxetine was given at the dose of 10 mg/kg/day orally. L-theanine was orally fed at a dose of 100 mg/kg/day. Gene expression exploration was executed using quantitative real-time PCR (qRT-PCR) to assess changes in stress-related and neuroprotective genes. Histological examinations of brain tissue were conducted to observe neuronal damage. Results: The UCMS group’s BDNF, GABRA1, and Nr3c1 gene expression levels were significantly downregulated (p<0.05), when compared to the Control group, whereas the L-theanine-treated UCMS groups’ gene expression points were significantly upregulated (p<0.05) than the fluoxetine treated UCMS group (positive control), when compared to the UCMS group. Conclusion: L-theanine effectively reduces UCMS-induced neuronal damage in Wistar rats by modulating gene expression. This highlights its potential as a therapeutic agent for stress-related neuronal damage. Further studies are warranted to explore its clinical applications in stress-related disorders.